Supermarket contracts and smallholder farmers: Implications for income and multidimensional poverty - Ogutu, Sylvester O.; Ochieng, Dennis O.; Qaim, Matin (2019)
The food retail sector in many developing countries is transforming with a rapid growth of modern supermarkets. Supermarkets are not only influencing how food is sold to consumers, but also how agricultural products are sourced from farmers. Especially for the procurement of fresh fruits and vegetables, supermarkets often contract farmers directly to ensure consistent, high-quality supply. Previous studies analyzed the effects of supermarket contracts on smallholder farmers’ income. However, most existing studies relied on cross-section data and focused on the estimation of average income effects. Possible implications for other dimensions of household welfare were hardly examined. We add to this literature by using panel data from smallholder vegetable farmers in Kenya and econometric models with household fixed effects to estimate average and heterogeneous treatment effects of supermarket contracts on income and multidimensional poverty. On average, supermarket contracts increase per capita income in smallholder farm households by 60%. We also find significant reductions in income poverty and multidimensional poverty. Quantile regressions show that farmers in all income groups benefit, but richer households benefit more than poorer ones in absolute terms. On the other hand, supermarket contracts cause the strongest reductions in multidimensional deprivations among the poorest households.